2008
DOI: 10.1177/0886260508316479
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Psychometric Typology of Child Molesters

Abstract: Cluster analysis of psychometric data measuring offense-specific and socioadequacy problems from a sample of 437 untreated child molesters was carried out. This analysis identified three clusters: Cluster 1 contained men who reported low levels of self-esteem and intimacy and an inability to deal with negative emotions, Cluster 2 contained men who demonstrated a poor understanding of the harm caused to their victims, and Cluster 3 contained offenders who had global offense-specific and socioaffective problems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Two studies have explored these relationships indirectly using cluster analysis (Beech, 1998;Mandeville-Norden & Beech, 2009). Beech (1998) used cluster analysis with a sample of sexual offenders against children on a battery of psychological measures and found that the group highest in emotional congruence with children also had the most problematic levels of social inadequacy (i.e., low self-esteem, loneliness, under-assertiveness, and personal distress [inability to handle negative emotions]), immaturity, and beliefs supportive of sexual offending against children.…”
Section: Blockagementioning
confidence: 99%
“…Two studies have explored these relationships indirectly using cluster analysis (Beech, 1998;Mandeville-Norden & Beech, 2009). Beech (1998) used cluster analysis with a sample of sexual offenders against children on a battery of psychological measures and found that the group highest in emotional congruence with children also had the most problematic levels of social inadequacy (i.e., low self-esteem, loneliness, under-assertiveness, and personal distress [inability to handle negative emotions]), immaturity, and beliefs supportive of sexual offending against children.…”
Section: Blockagementioning
confidence: 99%
“…High Deviance men were more likely to be reconvicted at two-year (3/26) and five-year (4/9) follow-up periods (13% and 44%, respectively) than the Low Deviance men (4% or 1/25, and 10% or 1/10, respectively). However, more recently, Mandeville-Norden and Beech (2008) examined the psychometric profiles of 437 child abusers who were about to enter a probation community sex offender treatment programme. Cluster analysis indicated that for this sample a three-factor solution was optimal in partitioning the data, and further analyses suggested the three groups were significantly different in their overall psychometric test scores.…”
mentioning
confidence: 99%
“…Overall, there are a complex range of factors associated with the ‘chances’ of someone maltreating children and the truth of the matter is that largely we do not know why some people hurt children, when others in similar circumstances do not. The development of psychometric typologies in the sexual abuse arena shows promise in understanding the motivation and potential treatment of sex offenders (Finkelhor, ; Mandeville‐Norden and Beech, ; Robertiello and Terry, ), but for physical abuse, neglect and emotional abuse, contributing factors and parental characteristics are far more diverse and most parents show strong commitment to their children even when they are involved in care proceedings (Thoburn et al ., ). The families known to child protection services tend to have a high incidence of domestic abuse, substance misuse and parental mental ill‐health: Recent analysis of serious case reviews (undertaken in England when a child has died or there has been a ‘near miss’) showed that over half the children lived with current or past domestic abuse, almost two‐thirds lived in a household where a parent or carer had a mental illness and a substantial number of parents were misusing drugs or alcohol (Brandon et al ., ).…”
Section: Risks and Risk Factors: Models And Predictive Instrumentationmentioning
confidence: 99%